Nilai-Nilai Keagamaan Dalam Novel Hasein Karya Adelia Nurrahma Dan Implikasinya Terhadap Pembelajaran Teks Novel Di SMA - Fioca Rifka Fortuna (Cetta: Jurnal Ilmu Pendidikan, 2021)
The purpose of this study was to describe the religious values in the novel Hasein by Adelia Nurrahma. The object of this research is the novel Hasein by Adelia Nurrahma and this research is about religious values in the novel Hasein by Adelia Nurrahma. This type of research is a qualitative research with descriptive method. The data of this research is qualitative data, namely the data contained in words, phrases, and sentences that contain religious values in the novel Hasein by Adelia Nurrahma. The data collection techniques for this research are identifying data on characters, identifying data on events, and identifying data on religious values in Adelia Nurrahma's Hasein novel. The data analysis techniques of this research are (1) data reduction, (2) data presentation, (3) data leveraging. Based on the results of the study, the religious values contained in the novel Hasein by Adelia Nurrahma were found. First, the moral values of Islam with three indicators, namely, moral values towards Allah SWT, moral values towards oneself, and moral values towards humans. Second, the value of Islamic faith with six indicators, namely, the value of faith in Allah SWT, the value of faith in the angels, the value of faith in the holy book Al-Quran, the value of faith in prophets and apostles, the value of faith for days, the value of faith in Qadha and Qadhar.